(untitled) (Proceeding of SINERGY, 2026)
This study aims to analyze the influence of ambiance, food quality, service quality, and menu diversity on customer satisfaction at Richesse Factory in Purwokerto. The research a quantitative approach using a survey method. The population consists of customers who made purchases at the Richeese Factory in Purwoker at least twice, with the total population size being unknown. The sampling technique applied is non-probability sampling, specifically purposive sampling. The sample size was determined using the Cochran formula, resulting in 97 respondents; however, the analysis was conducted on 100 respondents. The data were analyzed using multiple linier regression analysis with the assistance of IBM SPSS version 27. The regression formula is represented in the following manner: Y = 5,898 + 0,275X1 + 0,214X2 + 0,1863 + 0,286X4 + e. The Adjusted R Square value of 0,602 indicates that the variation in customer satisfaction is explained by the variables included in the model, while the remaining 39,8% is influenced by other factors. The F-test verifies the overall significance of the model. (F= 38.411 > F-table= 2.47). Furthermore, the t-test results show that ambiance, food quality, service quality, and menu diversity each have a positive and significant effect on customer satisfaction. The findings imply that fast-food restaurant managers should focus on improving ambiance quality, particularly noise control, enhancing nutritional information transparency to strengthen perceptions of food quality, optimizing service responsiveness in complaint handling, and continuously developing relevant menu innovations aligned with customer preferences. Future research is recommended to incorporate additional variables such as price perception, customer experience, or customer loyalty and extend the research scope to different regions or types of restaurants to improve the generalizability of the findings.